Management of young teak plantations in Panama - effect of pruning and thinning - León Radío, María Inés; Martín Delgado, Daiana (2014)
On high quality wood species, thinning and pruning are compulsory management that must be done not only in early stages but also often during later development of the plantation in order to improve wood quality and growth of individual high-quality trees. In this thesis two trials were carried out to determine the adequate intensities of first thinning and pruning in a teak plantation in order to find the optimum early management to reach the best growth in yield and quality terms. In trial 1 pruning at 3 and 5 metres was combined with a thinning of the 35 % of the initial number of trees, 1111 tree per ha, which meant 15% removal of basal area. In trial 2 four thinning intensities were analyzed: 0, 25, 35, 45 % of the initial number of trees (15, 20 and 30 % of basal area). The variables observed in the different treatments after six months, were analysed using the measurements of diameter, height and form factor. With this data, the increment of height, diameter, basal area and volume according each treatment were calculated. The measured stem-volumes were compared with stem-volume estimated by a function developed by Diego Pérez and Markku Kaninnen, 2003, for teak plantations in Costa Rica that uses only diameter at breast height as independent variable. It was found that this function for teak stem volume can be used for calculating teak wood volume in the Darién region of Panama.